2008
DOI: 10.1111/j.1460-9568.2008.06516.x
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic excitability during increased synaptic activity in rat neocortical L5 pyramidal neurons

Abstract: Recent years have seen increased study of dendritic integration, mostly in acute brain slices. However, due to the low background activity in brain slices the integration of synaptic input in slice preparations may not truly reflect conditions in vivo. To investigate dendritic integration, back-propagation of the action potential (AP) and initiation of the dendritic Ca(2+) spike we simultaneously recorded membrane potential at the soma and apical dendrite of layer 5 (L5) pyramidal neurons in quiescent and exci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…To induce somatic depolarization we increased synaptic activity in the slice by bathing with ACSF 2 (ACSF with increased K + and reduced Ca 2+ concentration). We have previously shown that this modified ACSF increases synaptic input to cortical neurons leading to somatic depolarization (Bar-Yehuda and Korngreen, 2007; Bar-Yehuda et al, 2008). We have reported that the average membrane potential depolarized by 5–7 mV while the membrane potential variance increased almost 10-fold from 0.03 to 0.4 mV 2 (Bar-Yehuda and Korngreen, 2007; Bar-Yehuda et al, 2008).…”
Section: Resultsmentioning
confidence: 94%
See 4 more Smart Citations
“…To induce somatic depolarization we increased synaptic activity in the slice by bathing with ACSF 2 (ACSF with increased K + and reduced Ca 2+ concentration). We have previously shown that this modified ACSF increases synaptic input to cortical neurons leading to somatic depolarization (Bar-Yehuda and Korngreen, 2007; Bar-Yehuda et al, 2008). We have reported that the average membrane potential depolarized by 5–7 mV while the membrane potential variance increased almost 10-fold from 0.03 to 0.4 mV 2 (Bar-Yehuda and Korngreen, 2007; Bar-Yehuda et al, 2008).…”
Section: Resultsmentioning
confidence: 94%
“…We have previously shown that this modified ACSF increases synaptic input to cortical neurons leading to somatic depolarization (Bar-Yehuda and Korngreen, 2007; Bar-Yehuda et al, 2008). We have reported that the average membrane potential depolarized by 5–7 mV while the membrane potential variance increased almost 10-fold from 0.03 to 0.4 mV 2 (Bar-Yehuda and Korngreen, 2007; Bar-Yehuda et al, 2008). We have also reported that the input resistance decreased by ~10 MΩ when ACSF was replaced with ACSF 2 and that the current threshold of the neuron decreased approximately by half from 280 to 130 pA (Bar-Yehuda and Korngreen, 2007; Bar-Yehuda et al, 2008).…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations